2019
DOI: 10.1182/blood-2019-124870
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Elotuzumab in Combination with Pomalidomide, Bortezomib, and Dexamethasone in Relapsed and Refractory Multiple Myeloma

Abstract: Background Elotuzumab is an approved monoclonal antibody targeting SLAMF7 on plasma and NK cells that enhances the activity of lenalidomide, pomalidomide, and bortezomib in multiple myeloma (MM). A recent study showed improved outcomes with the combination of pomalidomide, bortezomib, and dexamethasone vs. bortezomib and dexamethasone in relapsed or refractory MM (Richardson PG et al., Lancet Oncol 2019). We therefore studied elotuzumab with pomalidomide, bortezomib, and dexamethasone (elo-PVD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…with pomalidomide-based combinations (Attal et al 2019;Richardson et al 2019) and will represent a formidable therapeutic challenge in the near future. A recent trial reported responses in 48% of daratumumab-exposed patients and acceptable toxicity with a quadruplet regimen of elo/pom/dex and bortezomib (Yee 2019), further corroborating our findings.…”
Section: Discussionsupporting
confidence: 91%
“…with pomalidomide-based combinations (Attal et al 2019;Richardson et al 2019) and will represent a formidable therapeutic challenge in the near future. A recent trial reported responses in 48% of daratumumab-exposed patients and acceptable toxicity with a quadruplet regimen of elo/pom/dex and bortezomib (Yee 2019), further corroborating our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Samples for our exploratory test cohort were acquired from patients at remission stage or while undergoing induction therapy (n=16, Table 1 ). Samples for our validation cohort were acquired from 45 patients ( Table S1 ) treated within a multi-center phase II trial testing elotuzumab with pomalidomide-bortezomib-dexamethasone (elo-PVD) for RRMM 37 . All samples for this portion of the trial were retrieved at screening and at cycle 3 day 1 (C3D1) of elo-PVD.…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
“…Prior pomalidomide exposure was permitted. 54 Results were released in 2019; 48 patients were enrolled, median number of prior lines of therapy was 3. At a median follow-up of 18.8 months in 46 evaluable patients, median PFS was 9.8 months, and ORR was 61%; ORR for patients with previous pomalidomide was 43%, previous carfilzomib 46% and previous anti-CD38 46%.…”
Section: Quadruplet Combinations With Pomalidomide–dexamethasone Back...mentioning
confidence: 99%